Statistics for psychology - Aron, Arthur (Prentice Hall, 1994)
In this third edition of this statistics textbook, the authors have tried to maintain things that have been especially appreciated, while reworking the book to take into account the feedback they have received, their own experiences, and advances and changes in the field of statistics. The authors have also added new pedagogical features to make the book even more accessible for students. Features in this edition include: definitional formulas, verbally and numerically taught procedures, up to date statistical theory and application, and a look at advanced procedures.